2019
DOI: 10.31235/osf.io/hqcgy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engaging Students through Blended Learning Activities to Augment Listening and Speaking

Abstract: Present study examines pedagogically the effect of blended learning activities to augment listening and speaking at tertiary level. Teachers provided content online that allowed measuring the students' engagement, satisfaction, teacher's role, and content and examination. Using the tools online on Blackboard®, discussion on forums and listening activities, the teacher provided the blended learning activities. The three-step strategy (3SS) framework was adopted for language learning.It provided students strateg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Among the four language skills, speaking and listening received less attention in the existing literature than reading and writing. Some studies reported on the impact of blended learning activities on the augmentation of English listening and speaking skills in the Bangladeshi, Indonesian and Omani contexts (Rabbi, Zakaria and Tonmoy, 2017 ;Rahmawati, 2019;Pramila and Thomas 2019 ;Hussein Alsowayegh et al, 2019 ;Grgurovic 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the four language skills, speaking and listening received less attention in the existing literature than reading and writing. Some studies reported on the impact of blended learning activities on the augmentation of English listening and speaking skills in the Bangladeshi, Indonesian and Omani contexts (Rabbi, Zakaria and Tonmoy, 2017 ;Rahmawati, 2019;Pramila and Thomas 2019 ;Hussein Alsowayegh et al, 2019 ;Grgurovic 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…EFL language instructors and their students in almost all schools in Saudi higher learning institutions are now using blended learning (BL) and virtual learning environments (VLEs) to deliver and teach e-courses over e-learning platforms to help promote teaching and learning, especially in foreign language education. Using these e-learning technologies has become widespread not only locally, but globally as well due to the rampant spread of COVID-19 pandemic (Al Thaqafi, 2020;Al-Qahtani, 2019;Altobaiti, 2020;Obaid, 2020;Alsowayegh, Bardesi, Garba, & Sipra, 2019;Bukhari & Basaffar, 2019;Gulnaz, Althomali, & Alzeer, 2020;Ja'ashan, 2020;Obaid, 2020). More specifically, BL and VLEs have been utilized in language learning and teaching environments over the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have examined the usefulness of using technology in online and blended learning in Saudi universities. These studies have found that online learning has been an effective solution to continuing teaching and learning and has many advantages, including high level of accessibility, saving money, time, and effort, and class and lecture recording (Alsowayegh et al, 2019;Ali, 2017;Alowedi, 2020;Bukhari & Basaffar, 2019;Gulnaz et al, 2020). Ali (2017) found that using the Blackboard platform demotivated some language learners and motivated others, whereas Alfadda and Mahdi (2021) found a significant correlation between the use of Zoom by Saudi university students and their positive perception of technology's utility in EFL classrooms.…”
Section: The Advantages Of Online and Blended Learningmentioning
confidence: 99%
“…Madrasati and Blackboard are the two most prominent tools that have been used in Saudi Arabia in the wake of the pandemic and social distancing rules. A number of local researchers have undertaken the task of investigating the effectiveness and appropriateness of these tools in different institutions in Saudi Arabia, the findings of which indicate that online tools such as Blackboard have contributed significantly to the success of online education in the kingdom (Alsowayegh et al, 2019;Ali, 2017;Alowedi, 2020;Bukhari & Basaffar, 2019;Gulnaz et al, 2020). Although many studies have looked into the concept of teaching and learning online, there seems to be a lack of empirical evidence on the challenges and difficulties that EFL students and teachers encounter during writing lessons with a special focus on online corrective feedback.…”
Section: Introductionmentioning
confidence: 99%